The First Documentary Evidence for Qara Qorum from the Year 635/1237–8 - Heidemann, Stefan; Kelzenberg, Hendrik; Erdenebat, Ulambayar; Pohl, Ernst (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The history of the foundation of Qara Qorum is clouded by contradicting evidence. All information came either from later memorial inscriptions or from chronicles written at least decades after the events at different places. The joint excavation of the Mongolian Academy of Science and the Bonn University yielded the earliest dated primary documentary evidence of Qara Qorum, a coin, struck in the year (6)35 H./1237–8 A.D., about two years after the supposed construction of the palace of Ögedai in 1235. The coin was presumably struck within the palace compound, in a workshop under the control of the Muslim community. It was found within a coppersmiths workshop located in the Chinese commercial area of the city. The article will be available as a PDF in the near future.